Keragaman dan Prevalensi Nematoda Parasit Usus pada Monyet Ekor Panjang (Macaca fascicularis) di Kawasan Wisata “Masjid Saka Tunggal” - Edy Riwidiharso; Erie Kolya Nasution; Heru Triaji (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Nematode parasites generally found around the world. Research on intestinal parasitic nematodes in long-tailed monkeys (Macaca fascicularis) has been carried out in Cikakak Village, Banyumas Regency. The aims of the research was to find out the diversity and prevalence of Nematodes parasite on long tail monkey. Survey methods was used in this research with determine the eggs of the nematodes parasite on faeces of 30 adults and 30 adolescence of monkey. The results of the study found five types of intestinal parasitic nematodes classified as